1992
DOI: 10.1007/bf01981500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxicity, pathology, and treatment of cyclohexylmethylphosphonofluoridate (CMPF) poisoning in rhesus monkeys

Abstract: Cyclohexylmethylphosphonofluoridate (CMPF) is an organophosphate cholinesterase inhibitor with military significance. The purpose of these studies was 1) to determine the acute toxicity of CMPF in the male rhesus monkey, 2) to evaluate the efficacy of pyridostigmine (PYR) pretreatment plus atropine and oxime (2-PAM or H16) treatment, and 3) to evaluate the pathological consequences of acute poisoning. An i.m. LD50 of CMPF was estimated using an up-and-down dose selection procedure and 12 animals. The 48-h and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The mechanism of this protection seems to be the preoccupation by the carbamate of ChE reactive sites, which become unavailable to the OP ChE inhibitor, with subsequent restoration of enzymatic activity due to the reversible decarbamylation of ChE. This phenomenon is the basis for the use of PB as a prophylactic of nerve agent intoxication (Dirnhuber et al, 1979;Leadbeater et al, 1985;Kluwe et al, 1987;Keeler et al, 1991;Koplovitz et al, 1992). The therapeutic target for this application of PB has been to maintain inhibition of plasma butyrylcholinesterase (BuChE) between 20 and 40%.…”
mentioning
confidence: 99%
“…The mechanism of this protection seems to be the preoccupation by the carbamate of ChE reactive sites, which become unavailable to the OP ChE inhibitor, with subsequent restoration of enzymatic activity due to the reversible decarbamylation of ChE. This phenomenon is the basis for the use of PB as a prophylactic of nerve agent intoxication (Dirnhuber et al, 1979;Leadbeater et al, 1985;Kluwe et al, 1987;Keeler et al, 1991;Koplovitz et al, 1992). The therapeutic target for this application of PB has been to maintain inhibition of plasma butyrylcholinesterase (BuChE) between 20 and 40%.…”
mentioning
confidence: 99%
“…On the other hand, equimolar dosing of oximes is useful when in vitro and in vivo results should be compared. Although cyclosarin is an extremely strong inhibitor of human AChE and butyrylcholinesterase (EC 3.1.1.8) and has obviously an even higher potency than the nerve agent soman 9 , in vivo, cyclosarin is less toxic than soman in several species, including non-human primates 10 , indicating different toxicokinetic behaviour. It was already shown that intoxications with cyclosarin are rather resistant to convential oxime therapy 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this protection appears to be the pre-occupation by the carbamate of ChE reactive sites, which become unavailable to the OP ChE inhibitor, with subsequent restoration of enzymatic activity due to the reversible decarbamylation of ChE. This phenomenon is the basis for the use of PB as a prophylactic of nerve agent intoxication Leadbeater et al, 1985;Koplovitz et al, 1992;. The therapeutic target for this apphcation of PB has been to maintain inhibition of plasma butyrylcholinesterase (BuChE) between 20% to 40%.…”
Section: 001mentioning
confidence: 99%
“…The carbamate ChE inhibitor pyridostigmine bromide (PB) has been fielded as a prophylactic treatment against OP ChE inhibitors by the US Armed Forces and used in the Persian Gulf War ; (Leadbeater et al, 1985); (Koplovitz et al, 1992); ; . Although acute intoxication with OP ChE inhibitors and the protective effect of PB on this phenomenon have been extensively studied in animals ; (Sidell, 1974); , the potential long term harmful effects of low level (subsymptomatic) exposure to OP ChE inhibitors, alone or in combination with PB have received little attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation